Kekuatan Modal Sosial Pada Kelompok Tani Jagung Di Desa Suwaan Kecamatan Kalawat Kabupaten Minahasa Utara - Tirayoh, Kezia Aglien Mega; Sendow, Martha Marejke; Rengkung, Leonardus Ricky (AGRI-SOSIOEKONOMI, 2024)
This research aims to describe the social capital strengths of the Anugrah Corn Farmer Group in Suwaan Village, Kalawat District, North Minahasa Regency. The study took place over 3 months from August to October 2023. It was conducted within the corn farmer group in Suwaan Village, Kalawat District, North Minahasa Regency. Data for this research were collected using primary sources through direct interviews with village elders/secretaries and community members of the farmer group, supported by observations and questionnaires as data collection tools. Secondary data were obtained from relevant agencies such as the village office and the internet to supplement primary data. Purposive sampling was employed to select participants, specifically the Anugrah Corn Farmer Group in Suwaan Village, totaling 11 farmers. Data analysis utilized descriptive analysis with Likert scale measurements using tables and figures. The research findings indicate that social capital played a significant role: the total trust dimension score was 171, categorized as very high; the total norm dimension score was 153, also categorized as very high; and the network dimension yielded an overall score of 492 from 11 respondents of the Anugrah Corn Farmer Group, representing 93.18%, categorized as very high.